1991
DOI: 10.1063/1.460892
|View full text |Cite
|
Sign up to set email alerts
|

Chemical etching of vicinal Si(111): Dependence of the surface structure and the hydrogen termination on the pH of the etching solutions

Abstract: Homogeneous hydrogenterminated Si(111) surface formed using aqueous HF solution and waterInfrared spectroscopy is used to study the etching process of stepped Si ( 111 ) 9° surfaces as a function of the pH of the etching HF solutions. This process results in complete H termination of the silicon surface, including terraces, steps, and defects; the surface structure can therefore be well studied using infrared (lR) spectroscopy. Polarized IR absorption spectra of the Si-H stretching vibrations (i.e., in the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 312 publications
(211 citation statements)
references
References 29 publications
11
199
0
Order By: Relevance
“…The broadness would cause the wide vibration energy by H 2 O adsorption on the Si surface in flowing pure water [10]- [12]. Di-2-ethylhexyl sulfosuccinate sodium salt (aerosol OT) as surfactant is C 8 Figure 4. The spectra showed CH x stretching vibration, and the peak intensity was increased with the flowing time.…”
Section: Resultsmentioning
confidence: 99%
“…The broadness would cause the wide vibration energy by H 2 O adsorption on the Si surface in flowing pure water [10]- [12]. Di-2-ethylhexyl sulfosuccinate sodium salt (aerosol OT) as surfactant is C 8 Figure 4. The spectra showed CH x stretching vibration, and the peak intensity was increased with the flowing time.…”
Section: Resultsmentioning
confidence: 99%
“…It appeared that selective Dy etching by strong alkaline solutions occurs mainly at the step edges, which is comparable to wet etching of SrTiO 3 (001) and Si (111) surfaces. 17,18 As a result, the etching rate severely depended on the surface morphology, which varied from substrate to substrate, independent of the miscut angle. Therefore a surface roughening step was introduced to increase the number of step edges.…”
Section: Substrate Treatmentmentioning
confidence: 99%
“…6 Pietsch et al reported on the ex situ STM results of Si/SiO 2 interface obtained in concentrated HF solution, which composed of small islands and pits with atomic roughness. 7 More detailed results of the preparation of atomically flat Si(111)-H surface can be seen in Behm's work in which the appearance of Si(111) surface investigated by ex situ STM was drastically changed with immersion time in 40% NH 4 F solution.…”
Section: Introductionmentioning
confidence: 99%